Kepemimpinan Transformatif dalam Tata Kelola Pegawai di Kecamatan Duren Sawit Jakarta Timur - Primasari, Dewi; Biridlo’i Robby, Uchaimid; Ardiyansah, Ardiyansah (ANTASENA: Governance and Innovation Journal, 2024)
The aim of this research is to determine and analyze: a) transformative leadership in employee governance in Duren Sawit District, East Jakarta. b) factors inhibiting and supporting transformative leadership in employee governance in Duren Sawit District, East Jakarta. c) efforts to improve employee governance in Duren Sawit District, East Jakarta. The research method uses descriptive qualitative methods. The research instrument was conducting in-depth interviews and documentation. The results of the research are: a) Transformative leadership in employee governance in Duren Sawit sub-district, East Jakarta is still in process with all its advantages and disadvantages, namely leadership that can make the organization better by means of innovation, policy and intelligence by means of empowerment, stewardship and accountability. The sub-district head's transformative leadership in improving employee governance with indicators of charismatic behavior, intellectual motivation, intellectual stimulation, giving attention and consideration to individuals. b) Factors inhibiting transformative leadership in employee governance in the Duren Sawit sub-district, East Jakarta, namely leaders who are not yet optimal in giving attention to all their employees so that they work optimally, human resources who are less skilled and less competent in carrying out their duties and a lack of technological devices and digital applications that can support organizational policies. Meanwhile, supporting factors include better work motivation, transparency in activities, clear organizational structure and main functional duties to support improvements in the organization as well as innovation, creativity and technology transfer that make it easier to improve services. c) Efforts to improve governance. Employee management in Duren Sawit sub-district, East Jakarta is carried out by improving the government's internal control system, training for employees who can transfer knowledge, synergistic collaborative efforts between leadership and staff in accordance with applicable regulations and good planning so that all programs can run well